Prevalence and Pattern of the Elongated Styloid Process among a Saudi Population - Dafalla, Salah Eldeen (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: The objectives of this study were to assess the elongation of the styloid process (SP) on digital panoramic radiographs (DPRs) and to evaluate the prevalence of the elongation according to age, sex, and type. Materials and Methods: DPRs of 198 geriatric edentulous patients were analyzed. The radiographic length of the SP was measured on both sides using the measurement toolbars on the accompanying analysis software. The student’s t-test, Chi-square test, and analysis of variance test were used for statistical analysis. Results and Discussion: The elongated SP was seen in 87 of the 198 patients. It was observed that as age increased, elongation of the SP increased with a male predominance. Type I elongation was more common than other types of elongation. Bilateral elongation was more commonly found than unilateral elongation, and both types of elongation were frequently seen in males compared to females. Conclusions: The prevalence of the elongated SP in the present study was higher than the other reports from edentulous patients.